Exploring Inappropriate Discourse Markers on Students Argumentative Essay: A Discourse Study - Hasanah, Rifatul; Basya, Dihliza; ., Ismaili; Sabartono, Ribut (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2022)
Effective usage of DMs can help both readers and writers to understand better.Many researchers point out that DMs are important thing in writing, but in another situation, there are still many students using inappropriate DMs in their writing. The goal of this study is to know inappropriate Discourse markers on their essay and also to know what are the factors behind it by studying argumentative essay using Fraser taxonomy and conducting interview.The result argumentative essay, it is found misused discourse markers and overused discourse markers. Total number of inappropriate DMs on students’ argumentative essay are 26 markers. Based on the interview, the researcher found some factors; lack of knowledge, lack of instruction and lack of the awareness about discourse markers.From the result of this study, it indicated that the students’ knowledge about discourse markers were limited. Besides, their essayswere less coherent and cohesive. As conclusion, limitation and recommendation were then discussed.